Possibilistic and stochastic analysis using for rubber‐like materials. Issue 1 (17th December 2018) - Penner, Eduard; Caylak, Ismail; Dridger, Alex; Mahnken, Rolf
Abstract: In many engineering applications the material behavior, e.g. hyperelasticity, is described by an appropriate mathematical model. However, those become uncertain due to different types of uncertainty such as variation in the manufacturing process, measurement errors and missing or incomplete information on material properties. This contribution presents a framework for an uncertain nonlinear elastic material model at large deformations. As a key idea uncertainties of a material are described by correlated uncertain parameters, which are modeled in the first case as possibilistic and in the second case as random variables.